Assessment of the dilution-neutralization method with a disinfectant according to the Colombian Technical Norm 5473 of 2007. - Arias-Palacios, Janeth; Grupo de Biotecnología Ambiental e Industrial (GBAI). Departamento de Microbiología, Facultad de Ciencias. Pontificia Universidad Javeriana, Bogotá, D.C., Colombia. (Pontificia Universidad Javeriana, 2012)
Objective. Evaluate the dilution-neutralization method proposed in the Colombian Technical Norm 5473/07, by using a gel, alcoholbased disinfectant. Materials and methods. This study was done using Pseudomonas aeruginosa ATCC 15442, Staphylococcus aureus ATCC 6538, and Enterococcus hirae ATCC 10541 as the assay microorganisms. The study was carried out at 20±1°C as obligatory temperature and additionally at 36±1°C. Four contact times between microorganisms and the disinfectant were evaluated (0, 2, 5 and 10 minutes). The assay was done both under clean conditions (0.3 g/L of bovine serum albumin), and unclean conditions (3 g/L of bovine serum albumin and 3g/L of sheep erythrocytes). Results. The implementation of this method produced precise results in all of the sixrepetitions used during the assay. The obtained results demonstrated a logarithmic reduction higher than five, demonstrating the bactericidal activity exerted by the disinfectant on the control microorganisms. The established experimental conditions and methodology did not affect negatively the growth of any of the strains of microorganisms. Similarly, the neutralizing used did not inhibit the development of the microorganisms of the assay. Conclusions. The method was verified by means of the fulfillment of the limits set by the rule. Our results suggest that the method evaluated by means of the implementation of the protocol established in the Colombian Technical Norm 5473/07, allows evaluating the effectiveness of a disinfectant under selected and controlled experimental conditions.Key words: disinfection, clean conditions, unclean conditions, dilution-neutralization method, logarithmic reduction.